2023
DOI: 10.1097/sla.0000000000005302
|View full text |Cite
|
Sign up to set email alerts
|

Circumferential Resection Margin is Associated With Distant Metastasis After Rectal Cancer Surgery

Abstract: Objective: To evaluate circumferential resection margin (CRM) as a risk factor for distant metastasis (DM) in rectal cancer. Summary of Background Data: The treatment of rectal cancer has evolved over the last decades. Surgical radicality is considered the most important factor in preventing recurrences including local and distant. CRM ≤1.0 mm is considered to increase recurrence risk. This study explores the risk of DM in relation to exact CRM. Methods: All patients treated with abdominal resection surgery fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…This study used this standard for CRM positivity. Some researchers believe that positive CRM is a risk factor for local recurrence and that the distance between the tumor and MRF is negatively correlated with the prognosis ( 12 , 27 ). A study on neoadjuvant therapy shows that even if patients with positive CRM undergo surgical resection of the lesion after neoadjuvant therapy, positive CRM is still a risk factor for local recurrence ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study used this standard for CRM positivity. Some researchers believe that positive CRM is a risk factor for local recurrence and that the distance between the tumor and MRF is negatively correlated with the prognosis ( 12 , 27 ). A study on neoadjuvant therapy shows that even if patients with positive CRM undergo surgical resection of the lesion after neoadjuvant therapy, positive CRM is still a risk factor for local recurrence ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…We explored the implications of pathologic features to identify the subgroup of patients with rectal cancer indicated for adjuvant chemotherapy. Surgical margin has been a well-known prognostic factor before neoadjuvant CRT era [ 3 , 24 , 25 , 26 , 27 ]. Quirke et al first reported that positive surgical margin increased local recurrence in 1986 [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we investigated patients who benefited from adjuvant chemotherapy based on pathologic factors. Surgical margin and perineural invasion are well-known prognostic features in rectal cancer [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. We investigated the role of adjuvant chemotherapy in patients with rectal cancer who received neoadjuvant CRT and curative TME in this multi-institutional study, according to the status of surgical margin and perineural invasion.…”
Section: Introductionmentioning
confidence: 99%
“…A positive CRM is associated with an increased risk for local recurrence and distant metastasis and worse overall survival rates . Although there has been some debate about what constitutes a negative CRM, the commonly accepted margin of 1 mm from the tumor is considered a negative resection …”
Section: Introductionmentioning
confidence: 99%
“…8,9 Although there has been some debate about what constitutes a negative CRM, the commonly accepted margin of 1 mm from the tumor is considered a negative resection. 10 To study and improve health care delivery and quality, valid quality measures must be identified and broadly reported. Strong quality measures are those for which compliance translates into improved patient outcomes.…”
mentioning
confidence: 99%